Associations between the concurrent use of clinical decision support and computerized provider order entry and the rates of appropriate prescribing at discharge - Patterson, M.E.; Marken, P.A.; Simon, S.D.; Hackman, J.L; Schaefer, R.S. (Applied Clinical Informatics, 2012)
Introduction: Electronic health record systems used in conjunction with clinical decision support (CDS) or computerized provider order entry (CPOE) have shown potential in improving quality of care, yet less is known about the effects of combination use of CDS and CPOE on prescribing rates at discharge.Objectives: This study investigates the effectiveness of combination use of CDS and CPOE on appropriate drug prescribing rates at discharge for AMI or HF patients.Methods: Combination use of CDS and CPOE is defined as hospitals self-reporting full implementation across all hospital units of CDS reminders, CDS guidelines, and CPOE. Appropriate prescribing rates of aspirin, ACEI/ARBs, or beta blockers are defined using quality measures from Hospital Compare. Multivariate linear regressions are used to test for differences in mean appropriate prescribing rates between hospitals reporting combination use of CDS and CPOE, compared to those reporting the singular use of one or the other, or the absence of both. Covariates include hospital size, region, and ownership status.Results: Approximately 10% of the sample reported full implementation of both CDS and CPOE, while 7% and 17% reported full use of only CPOE or only CDS, respectively. Hospitals reporting full use of CDS only reported between 0.2% (95% CI 0.04 – 1.0) and 1.6% (95% CI 0.6 – 2.6) higher appropriate prescribing rates compared to hospitals reporting use of neither system. Rates of prescribing by hospitals reporting full use of both CPOE and CDS did not significantly differ from the control group.Conclusions: Although associations found between full implementation of CDS and appropriate prescribing rates suggest that clinical decision tools are sufficient compared to basic EHR systems in improving prescribing at discharge, the modest differences raise doubt about the clinical relevance of the findings. Future studies need to continue investigating the causal nature and clinical relevance of these associations.
Keywords: Electronic health records and systems; clinical decision support; inpatient computerized provider order entry; medication management; guidelines and protocols; quantitative methodologies